Political and legal analysis of threats to the national security of the Republic of Kazakhstan in the context of globalization (Journal of actual problems of jurisprudence, 2021)
This article is devoted to the legal analysis of ensuring national security during the 30 years of independence of the Republic of Kazakhstan. It examines the legal problems of ensuring national security. An analysis of external threats to the national security of the Republic of Kazakhstan is also carried out. At the same time, special attention is paid to such threats as environmental degradation, the growth of illegal migration, and the food crisis. The article reveals the influence of international experience on the process of ensuring national security; recommendations are proposed for improving legislation and the activities of state bodies in the field of ensuring national security. When writing this study, such methods were used as structuralfunctional, systemic, comparative-legal, logical, linguistic, formally legal. The authors believe that in order to prevent the threat of international terrorism, it is necessary to strengthen national statehood, its functional power, to strengthen unity and national identity, to fundamentally and clearly defend their national interests in any international projects. It is also necessary to strengthen its defenses and international consistency. The article is relevant because, according to the message of President Tokayev K.K., the state should be hearing, and for the people living in this state, its citizens.Keywords: national security, security, external security, Constitution, law, threats to external security.